International economics - Asheghian, Parviz, 1943- (Minneapolis/St. Paul : West, 1995)
Theories of international trade. National policies, international organizations and agreements, and recent political events affecting international trade. International monetary relations. International economics and developing nations. Foreign direct investment and multinational corporations.
Keywords: Economics; International trade; International trade; International economic relations; International economic relations -- Case studies; International trade -- Case studies